Numerical simulation of springback and twisting of stamped thin U-shaped copper alloy sheets with a change of the blank alignment - Ha, Giap Xuan (Vietnam Journal of Mechanics, 2023)
An experimental database of springback and twisting of U-shaped elongated structures is available from a previous study. The materials are copper alloys: pure Cu, CuBe2, and CuFe2P, provided in thin sheets of thickness around 0.1 mm. After deep-drawing of rectangular blanks, which can be aligned with the tools or slightly misaligned, and tool withdrawal, the U-shaped structure exhibits an opening of the section (2D springback) and twisting (3D springback). Characteristic features of the deformed geometry are significantly different for the three alloys. This study is directed to understand the origin of that difference with a numerical simulation of the process. The mechanical behaviour of the materials was investigated in tension and hydraulic bulge test, out of comparison’s sake and to derive the hardening law over a strain range representative of the process. Finite element simulations are performed using the von Mises criterion coupled with isotropic hardening, to compare the predicted forming load and springback parameters with experimental values.